59 HORMONAL RISK FACTORS AND BREAST TUMOR CHARACTERISTICS IN PRE-MENOPAUSAL AFRICAN AMERICAN AND CAUCASIAN WOMEN: A PRELIMINARY ANALYSIS. (1st March 2005) - Ogutha, J.; Hall, M.; Elliott, D.; Cummings, S.; Cao, D.; Olopade, O. I.
Abstract : Background: Breast cancer is the second leading cause of cancer-related death in the United States. Although racial differences in incidence and mortality are well recognized, these differences remain largely unexplained. The role of estrogen in tumorigenesis is well documented, but few studies have focused on risk factor analysis in pre-menopausal women. Methods: African American women (n = 64) and Caucasian women (n = 36) with histologically confirmed breast cancer diagnosed before age 50 and healthy age-matched (± 5 years) controls (n = 39 African Americans, n = 28 Caucasians) ascertained in a hospital setting were enrolled in the study. Self-report questionnaires were administered and tumor data were abstracted from pathology/mammogram reports. Hormonal risk factors, specifically age at menarche, age at first live birth, number of pregnancies, breastfeeding, body mass index (BMI), and oral contraceptive (OCP) use, as well as tumor size, tumor grade, and estrogen receptor (ER) status were analyzed. Results: Cases and controls were similar on all variables except age at diagnosis and age at study entry (p = 0.0008), as the controls were matched ± 5 years. There was no statistically significant difference in mean age at diagnosis between African American and Caucasian patients (p = 0.51). African American women had higher BMI (p = 0.01), higher mean number of pregnancies (p = 0.02), younger age at first live birth (p ≤ 0.01), and they were less likely to breastfeed for a month or longer (p ≤ 0.01)). Age at menarche, OCP use, and age at first OCP use were not statistically significant across racial/ethnic groups. ER negative tumors were more prevalent in African American women (p = 0.01). No significant associations between ER status and hormonal risk factors were detected using univariate analyses. However, when other variables were controlled, a logistic regression detected a marginally significant predictive effect of the number of pregnancies for ER status (p = 0.06). Conclusion: Differences in hormonal risk factors and tumor characteristics were detected in this small hospital-based cohort of pre-menopausal self reported African American and Caucasian women. African American women were more likely to have histologically more aggressive tumors and larger studies are necessary to examine the contribution of modulatable risk factors such as early pregnancy, obesity, and breastfeeding practices to the observed disparities in incidence and outcome.